Percepción del terror peruano entre 1900 y 1910: abordajes periodístico, político y religioso para el análisis de Cuentos malévolos de Clemente Palma - Delgado Del Aguila, Jesús Miguel (2021)
This paper aims to reconstruct the concept of terror in the first decade of the twentieth century. The temporal delimitation is due to the fact that in that period a compendium of horror stories was published, entitled Malevolent Tales (1904), of the Peruvian writer Clemente Palma. To achieve the semantic configuration of the aforementioned term, we resort to the documentation of journalistic sources of that environment (such as The Trade, The Press, Varieties, among others), to support the perception assumed of it. Through the confrontation of these discourses, the influence that the author receives on the part of the derived themes, such as the association of terror with criminality or the obscurantism developed by unbalanced people, is notorious. Likewise, the ideology and philosophy that are extracted are linked to atheism and everything that criticizes and questions the dogmas of the Judeo-Christian religion.